Perkembangan Karakter Kebijakan Politik Luar Negeri Indonesia Dari Masa Ke Masa - Ari Setyowati (Universitas Dehasen Bengkulu, 2023)
The history and development of Indonesia's foreign policy continues to change from time to time. Starting from the leadership of President Soekarno, where during Soekarno's leadership, Indonesia's foreign policy underwent a change, namely a policy that was originally not militant or tended to be diplomacy turned into a policy of struggle with a spirit of patriotism that was militant and confrontational in fighting imperialism and colonialism. The change of leadership from Soekarno to Soeharto marked a new chapter from the old order to the new order. Foreign policy during the Soeharto era had a low profile character, Indonesia's foreign policy was carried out with a softer approach and seemed friendly in its relations with foreign countries and tended to Western countries. Then the development of Indonesia's foreign policy after the reformation experienced development, the foreign policy of the Susilo Bambang Yudhoyono (SBY) era had a main target, which was more focused on increasing Indonesia's role and status in the international political arena. Furthermore, foreign policy in Jokowi's leadership can be seen with his goal of realizing diplomacy related to populist nature, which can be interpreted as a step towards realizing community diplomacy, so that Jokowi's foreign policy is more inward looking. Seeing that the character of foreign policy continues to undergo changes and developments, in principle the basis of a country's foreign policy is usually rooted in its history, ideology and constitution. However, in practice, foreign policy formulators are often influenced by various factors, namely interests, leadership and internal and international political dynamics at any given time.